Issuer surplus and the partial adjustment of IPO prices to public information - EDELEN, R; KADLEC, G (Journal of Financial Economics, 2005)
This study develops a model in which rational issuers maximize the expected surplus from going public by choosing an offer price that weighs the benefit of higher proceeds if the offer is completed against the cost of foregone surplus if the offer fails. Increases in the market valuation of comparable firms during the waiting period imply higher surplus associated with going public; issuers respond with a partial revision in the offer price to elevate the probability of completion. The model offers insights into many facts associated with initial public offering pricing, including partial adjustment to market returns, the inverse relation between withdrawal and market returns, the asymmetric price adjustment to up versus down market returns, hot-issue markets, and unconditional underpricing.